A Program Based on Communicative Language Teaching and Project-Based Learning to Develop Experimental Secondary School Students’ EFL Critical Writing, Persuasive Speaking and Collaborative Thinking. - Mohamed Ahmed, Ahmed Mahmoud; Al-Naggar , Bahaa El-Din; El-Salam Edris, Ahmed Abd (Journal of Neonatal Surgery, 2025)
The current study aimed to develop the EFL critical writing performance, persuasive speaking, and collaborative learning of experimental secondary stage students through a program based on integrating communicative language teaching and project-based learning. To achieve this aim, sixty second-year EFL experimental secondary stage students from Al-Lewaa Formal Secondary School, Al-Agouza Directorate, Gizaa Governorate, Egypt, were assigned into two groups: thirty students for the experimental group and thirty for the control group. The researcher administered a pre- and a post-test for the purpose of data collecting and analysis. The researcher measured the EFL critical writing and persuasive speaking performance level by designing an EFL critical writing and persuasive speaking test before and after the treatment. A scale was designed to measure the effect of the suggested program based on integrating communicative language teaching and project-based learning on the students’ collaborative learning. The instruments were administered before and after the treatment. Finally, the results of the study showed that the suggested program based on integrating communicative language teaching and project-based learning has a positive effect on developing the EFL critical writing and persuasive speaking performance of formal secondary stage students and on their collaborative thinking.. .